I Survived: Academic Life of Junior High School Learners in Online Distance Learning - Gamboa, Jerame N. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
The study aims to describe the academic life of the junior high school learners in online distance learning. Further, the study aims to know the challenges and ways to adapt in the online learning modality. Specifically, it sought to answer how are the junior high school learners described in terms of enrollment, cohort survival, drop-out rate, promotion rate, available resources, and source of internet connectivity; and what are the practices of the junior high school learners in adapting to online distance learning in terms of time management, study habits, comprehending the lessons, attending synchronous classes, and completing the requirements. The study utilized mixed methods research design, specifically a sequential-explanatory. Documentary records were utilized in the conduct of the study. A questionnaire was administered to 931 students from Grades 7- 10 students of a state university in Bacolor, Pampanga, Philippines. After which, a focused group discussion through virtual meeting was conducted to the 22 student-leaders. It was found out that despite of the various lockdowns and continuous threat of the COVID-19, online education modality had allowed education be served to the learners. With various practices on how to adapt with the “new normal”, learners were able to be deal with the online set-up. Challenges are still present and remain to be unavoidable but continuous interventions are being done to assure that quality, equitable, and accessible high school education is served. However, it is suggested to further improve the conduct of the online classes; concepts that were of challenge to the students should be address in the reopening of schools; intervention for the students’ social aspects should be taken into consideration; and continuous support must be given to the learners as well as to the teachers.